The Impact of Financial Technology, Financial Literacy, and Financial Performance on Investment Decisions - Hambali, Denny (Indonesian Business Review, 2024)
As the number of players in the capital market increases and technological developments affect how and when individuals choose to invest, understanding the dynamics that influence these decisions becomes increasingly important. The purpose of this study was to analyze the effect of financial literacy, financial performance, and financial technology on the decision to invest in the people of Sumbaw City on the Indonesia Stock Exchange (IDX). The population in this study is the people of Sumbawa City who have invested in the Indonesia Stock Exchange (IDX), the sampling technique used is purposive sampling with a sample size of 100 respondents. The data analysis technique used is structural equation modeling-partial least square (SEM-PLS) with a Liketr scale from a range of 1 to 4. The results showed that financial literacy, financial performance, and financial technology partially had a positive and significant effect on investment decisions in the people of Sumbawa City. Based on the results of this study, it can be concluded that a high level of financial literacy will increase investors' understanding of managing investment risk and making smarter decisions. The company's financial performance also affects investor confidence in making investments, while the use of financial technology can facilitate access to information and investment transactions so as to influence investment decisions